How computerised agents see the world - Colomb, Robert M. (Penerbit UTM Press, 2008)
Agents, which are more or less autonomous programs performing tasks on behalf of users, act by exchange of messages. The content of messages is regulated by agreements called ontologies among the interoperating parties. In order for interoperation involving complex objects to be successful, there are several meta-ontological requirements, notably the ability to identify the object in the appropriate context and the ability to tell which are its parts. These issues of identity and unity are central to the OntoClean meta-ontology and method. This paper shows how they apply to a typical e-commerce application under multiple levels of refinement of more abstract objects into their parts. The point is made that a community of agents must operate in a world which is at least moderated, not a fully open world.